Some Vector Valued Sequence Spaces Generated by Musielak- Phy Function Over 2-Normed Spaces - M Ofie; Nasution, M K M (Journal of Research in Mathematics Trends and Technology, 2019)
In this work, we introduced some new vector valued sequence spaces over 2-normed spaces using Musielak-Phy function Î¦ = (ðœ‘ ð‘› ) . We also studied some properties of these spaces.